The impact of motivation and teachers’ autonomy support on children’s executive functions - Sosic-Vasic, Zrinka; Keis, Oliver; Lau, Maren; Spitzer, Manfred; Streb, Judith (Frontiers in Psychology, 2015)
The present study investigates the interplay of executive functions, motivation and teacher’s autonomy support in school context. In a cross-sectional study design 208 students from different school types completed a standardized motivation questionnaire and processed two executive function tasks. All teachers who teach these students were asked about their autonomy supporting behavior by a standardized test. Multilevel analyses assessed the effects of the student’s motivation and their teachers’ autonomy support on student’s executive functions. Our results show considerable relationships between these variables: high executive function capacities came along with teacher’s autonomy support and student’s intrinsic motivation styles, whereas low executive function capacities were related to external regulation styles. The results indicate the importance of autonomy support in school instruction and disclose the need to popularize the self-regulation approach.